ANALYSIS OF IMPLEMENTATION OF NATIONAL HEALTH GUARANTEE IN REGIONAL GENERAL HOSPITALS ANDI MAKASSAU PAREPARE - Rusman Rusman (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction: Law No.40 of 2004 on Social Security as a form of government commitment in the implementation of the National Social Security, BPJS establishment by Act 24 of 2011 on BPJS. This study aims to obtain information about the readiness of stakeholders in the implementation of JKN in General Hospital Andi Makkassau parepare. Method: This research is qualitative. Determination of informants using purposive sampling as many as 12 people. Data collection began 12 May s / d 30 June 2014 shaped depth interview, observation and review of documentation, as well as the validity of the data was performed using tiangulasi. Informant is of the business of the National Health Insurance Health Office Parepare, Chief Marketing BPJS Health (Persero) Branch of Pare-Pare, business Andi National Health Insurance Hospital Makkasau Pare-Pare, business National Health Insurance (BPJS) Cempae Health Center, the National Health Insurance business (BPJS) Health Center Lakessi, business National Health Insurance (BPJS) Health Center, participants of the National Health Insurance. Result: The results shows that human resources (doctors) ready, and the physical condition of primary and secondary faskes tool is still lacking, there is no aspect of regulatory guidelines in terms of health insurance, then the socialization of Social Security, and JKN BPJS already implemented by the stakeholders ie infoman of Health Office Parepare PT. BPJS Health (Persero) bramch Parepare and Andi Makkasau Pare-Pare Hospital and health centers have also been carried out socialization so that community people are getting familiar with these three aspects. Conclusion: Implementation of national health guarantee in regional general hospital andi makassau parepare not running optimally